Renewable energy development in tow selected African countries: an overview and assessment - Yamusa II, Shehu Usman; Ansari, Abdul Haseeb; Mustafa, Maizatun (INSI Publications, 2013)
Government officials, academics, independent researchers and private investors have been working since the energy crises in the 1970s towards maximizing alternative and new renewable energy sources. The traditional sources of energy are based on exhaustible natural resources; therefore, the energy that is cleaner and sustainable for sustainable development of the world economy is a sine qua non. The economy of a country is measured with the consumption of energy per capita. Least developed and developing nations of Africa are hard pressed to increase their power generation and maximize other sources of energy. But due to their inherent limitations in terms of financial resources, lack of sophisticated technology, lack of sufficient foreign aid, and ever growing population, their energy needs are going to increase in times to come of financial institution to exploit the available sources for energy generation depend on that. This paper attempts to provide an overview and assess the situation in two selected African countries: Nigeria and Algeria. The paper identifies some barriers and explores the way forward in these countries for successful energy generation by all possible means.